The Potential of Developing Complex and Unique Fintech Solutions in Kraków’s Business Services Centres - Głowacki, Jakub (Journal of Public Governance, 2021)
The development of the concept of the Internet of Things and Internet of Services solutions gave rise to changes in the financial sector, especially in the area of Fintech. The aim of this article is to assess the potential for the development of Fintech solutions in outsourcing and offshoring firms operating in Krakow. The manuscript contains an analysis of a survey conducted among the employees of Krakow’s branches of business services centres carried out in order to determine the relationship between the technological changes that have occurred in companies in the last 5 years and the complexity and uniqueness of the services provided. The results of the analysis show that BSC companies in Krakow have a high potential to develop services in the field of new financial technologies. Research has shown a significant relationship between the technological changes that have occurred in the last 5 years in the BSC sector and the complexity and uniqueness of the services provided by this sector. Research results may be important for public authorities, which should support the development and embedding of BSCs through a number of activities.